The Hospital Problem : the Report of a Special Conference of Labour, Hospital, Medical and kindred Societies (London : The Labour Party ; printed at the Office of the British Medical Association, 1924)
1924 1924 1920s 12 pages 7 11. It would make all public hospitals free and open to everyone who would be likely to derive benefit from institutional treatment. 12. While doing this it would insist on the treatment offered being equal to that of the best voluntary hospitals in efficiency. 13. It would endeavour to forestall the necessity for so many hospital beds by a forward social policy generally, and in particular by establishing a " national minimum " in health and housing by abolishing all slums and undertaking a comprehensive housing scheme. The reaction of each one to these propositions will vary according to one's ideas on fundamental principles. To those who have leanings towards what is termed nationalization No. 1 will be a reasonable ideal, and all that flows from that will be accepted. To those who believe in independent action some of that proposition will be acceptable, at any rate to the extent of the assertion that "there should be a sufficient accommodation to deal with all cases requiring institutional treatment." Articles 2, 3, 4, 8, and 10 are common ground for all those who have considered the necessities of medical work; statements to much the same effect have appeared in reports of the British Medical Association, in the Dawson Report, and in others less well known. The help of the Labour party in attaining the aim set out in the second part of No. 10 would be very welcome, but has not hitherto been given in any large measure. What has been done in this direction has been wholly the work of philanthropists. As to No. 13, the medical profession has been for fifty years insistent that steps should be taken to abolish old slums and to prevent the formation of new slums, and much of the present enlightenment of public opinion in housing matters has been due to persistent medical teaching, and to the practical application of that teaching by doctors in municipal affairs. The thirteen propositions of the hospital policy of the Labour party taken alone would be a valuable expression of opinion on the part of thoughtful persons. But they do not stand alone. There are a series of statements within the document designed to lead up to the conclusions. Therefore these statements must be examined. The document begins : "At the present time, with rare exceptions, general hospitals are supported by voluntary contributions," and the term "general hospital" is used throughout as a synonym for voluntary hospital. The writers give no indication of the fact that the Poor Law infirmaries, which contain a greater number of beds than the voluntary hospitals, are in reality large general hospitals. The rest of this paragraph is a strange commentary on the chief recommendation of the report — that the one and only salvation for the hospitals of the country is State ownership and control — for the paragraph recites a long list of overlapping public authorities responsible for a large majority of the hospital beds in the country. If the State has not contrived in all these years, with the hitherto unlimited resources at its disposal, to unify its own system of statutory hospitals, what advantage to the sick person will arise from the absorption into this welter of State hospitals of the voluntary hospitals, which are admitted in this report to attain an ideal standard of efficiency? Under "Present Hospital Accommodation" we find : "Accommodation can best be reckoned by the number of hospital beds available for the treatment of general diseases and accidents, and it has been found on investigation that at the present time there are absurdly few in comparison with the number required to deal with the present population of Great Britain. In the United Kingdom there are 52,194 beds. . . . Taking 2 1/2 beds per 1,000 of the population as the lowest possible minimum for the whole country, the number required for a population of 43 millions is 160,000, which shows a deficit of 107,906 beds." It is misleading to reckon " general hospital " beds as the sole criterion of accommodation. Fever hospital beds are just as much part of the necessary equipment, and should count in the total; any lack of these and other special beds means an additional call on the " general hospital " beds. The ratio of 2 1/2 beds per 1,000 as a " standard " and the total of 52,194 beds in the country are both absurd. In London alone there are more beds than these, and the total ratio for the country far exceeds 2 1/2 per 1,000. There are something like 132,324 beds provided by the Poor Law authorities alone in England and Wales; some 36,000 for small-pox; some 11,500 for tuberculosis; some 126,500 for mental patients; some 7,670 for the "services"; and some 48,150 in voluntary hospitals — a total well over 362,000 beds in England and Wales, giving for a population of 38 millions a ratio of 10 beds per 1,000. This figure is better than that of the United States of America, where the ratio is 8 per 1,000. One wonders why the Labour party put forward these absurd figures. How much reliance can be placed on an argument or on a line of policy based upon premisses such as the figures quoted ? The worst feature of the document is entitled the "Anomalies of the Voluntary System." It is stated that an appointment in a voluntary hospital has a "monopoly value," so that "the number of appointments is jealously guarded, with the result that all big hospitals are badly understaffed." It would be interesting to see the data on which this statement is based. The British Medical Association has collected its own data. There are 151 voluntary hospitals in England and Wales with 100 or more beds. The returns for 109 of these show a ratio of visiting staff (physicians and surgeons, but not including specialists, residents, or clinical assistants) to beds as 1 to 21.74, whilst the ratio of residents only is 1 to 40.91. The ratio of the whole effective staff is something like 1 to 10. In the Poor Law infirmaries the ratio is far below 1 to 100. Under " Patients " it is stated : "Another cause of lack of confidence and a certain reluctance on the part of patients to enter a hospital is a widespread feeling that they may be made the subjects of experimental treatment." If this be correct, why those long waiting lists? And why the insistence that the clinics for venereal disease must be in these hospitals? Since it is false, the mere tittle-tattle of cranks, why give publicity to a statement that will increase the alleged fear to the detriment of the sufferers? On the " Choice of Patients " there are statements which imply a grave kind of abuse on the part of hospital staffs. It is averred that when private practitioners known to members of the staffs send patients to hospitals, the consultant gives preferential treatment to them; and again, that patients are sent to receive private consultations with the members of the staffs at their homes in the expectation that the payment of the fee therefor will advance the patient's chances of admission to hospital. These are allegations which should have been substantiated or not made. I know of one case, and one only, where a body of persons had the temerity to make such a railing accusation against a definite hospital. The rout of the accusers was complete. The following concentrated libel upon the administration, the doctors, and the nurses, may be quoted : "The system of 'patients' payments' for treatment in the general wards and out-patients' departments of the hospitals is also open to objection. There is a natural bias on the part of the management to admit those who can pay in preference to those who cannot, and, if the fee varies with the patient's means, to select those who pay most. ... It is difficult for the administration and the nursing staff not to show some slight difference in favour of 'pay patients.'" And lastly, the chances of filling the hospital's coffers leads to the crowding of patients, so that "the quantity of the doctor's work becomes more important than the quality." Such statements are absurd, for the medical and nursing staffs rarely know on what terms individual patients are admitted, and the doctor does not lend himself to such exploitation — he has too much respect for his work. The essence of the Labour party's policy appears to be an insistence that the voluntary hospitals must be swallowed up in State hospitals at all costs, for fear these charities may live to be a thorn in the side of a unified State scheme that is envisaged. "If the voluntary hospitals continue the system of patients' payments, and the public hospitals are free and open to all, which it is essential they should be, there will be a tendency for the former to drift into pay hospitals for the middle classes and the latter to be used by the necessitous poor only. There will then arise a service for the rich and a service for the poor, which is bad from every point of view, and will entail all the evils and odium of the present Poor Law institutions." Should the programme of the Labour party be realized, the prognostications may prove true. As it has been in religion and in education, so it will be in hospitals; for nothing will prevent the independent-minded seeking their own means of treatment as of worship and of education. And it may come to pass that in this instance the "establishment" will be held in less esteem than the "free institutions." British Medical Association Policy. So much for the ungrateful task of criticism. I now turn to the policy of the British Medical Association. Co-ordination of Effort. At the present there are voluntary and statutory hospitals scattered throughout the country, and for the most part without any general plan of covering the ground and none of co-ordination of effort. We believe this defect could be remedied if the mechanism of consultation between the several hospital authorities, public and independent, were provided. Uniformity we reject; it would in our view be disastrous to the progressive development of medicine. It would tend to stereotype practice, so that there would be lost that freedom for observation and thought which is the breath of life to medicine. Those of us who have had experience of public control know that this develops into an elephantine and pachydermatous stolidity against which the most dynamic of genius explodes in vain. Consultation would bring no such dangers. It would bring co-ordination of effort, and stimulate investigation by interchange of information and possibly of equipment and staff. To bring all hospitals to a uniform level of State control would be to find the "least common multiple"; to maintain 36/L41/1/8